Giant cyst of ovary - Ihosvany Brismat Remedios; Angel Reinaldo Gutiérrez Rojas (Revista Cubana de Medicina Militar)
Introduction: Large tumors have been described throughout history, including gynecological tumors, and ovarian tumors when they weigh more than 12 kg constitute a medical rarity. Tumor masses in lower hemiabdomen are frequent causes of consultation in general surgery. Within these, ovarian cysts are the most frequently diagnosed. Objective: To describe the case of a giant ovarian cyst in a patient who was treated in a general surgery consultation due to an increase in abdomen size of several years of evolution. Clinical case: The case of a female patient, with a history of health, which goes to the general surgery service due to an increase in abdomen volume, progressive, insidious of 2 years of evolution, is presented. Ovarian-dependent cystic mass is diagnosed and a cystic tumor of the ovary is found in the transoperative period, which in the histopathological analysis reports a serous ovarian cystadenoma. Conclusion: Ovarian tumors are not as frequent as those of the uterus and those of the breast, but they constitute the third group of benign and malignant tumors of women. The case was presented because of the infrequent result, the low frequency of reporting these cases, which brings knowledge to the medical community on the subject.